2017
DOI: 10.2169/internalmedicine.56.8081
|View full text |Cite
|
Sign up to set email alerts
|

Long-term Low-density Lipoprotein Apheresis in a Patient with Refractory Idiopathic Membranous Glomerulonephritis

Abstract: A 61-year-old Japanese man developed nephrotic syndrome (NS) due to idiopathic membranous glomerulonephritis (MGN). He received immunosuppressive therapy for two years, including prednisolone, cyclophosphamide, and cyclosporine A, but the NS persisted. Low-density lipoprotein apheresis (LDL-A) was initiated at a frequency of twice a month and continued for 9 years (203 sessions in total). His proteinuria reduced to less than 1 g daily after 9 years. LDL-A was stopped, and the NS has not relapsed for five years… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…Several published clinical cases have demonstrated the effectiveness of adding apheresis (double-filtration plasmapheresis (DFPP), plasma exchange) for patients with membranous nephropathy refractory to standard immunosuppressants, with a favorable evolution of nephrotic syndrome [ 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 ]. Various hypotheses, apart from the elimination of autoantibodies, were considered, including: Elimination of LDL cholesterol: Enhancing the bioavailability of immunosuppressants (cyclophosphamide, calcineurin inhibitors, and steroids) and mitigating the glomerular toxicity associated with dyslipidemia [ 25 , 26 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Several published clinical cases have demonstrated the effectiveness of adding apheresis (double-filtration plasmapheresis (DFPP), plasma exchange) for patients with membranous nephropathy refractory to standard immunosuppressants, with a favorable evolution of nephrotic syndrome [ 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 ]. Various hypotheses, apart from the elimination of autoantibodies, were considered, including: Elimination of LDL cholesterol: Enhancing the bioavailability of immunosuppressants (cyclophosphamide, calcineurin inhibitors, and steroids) and mitigating the glomerular toxicity associated with dyslipidemia [ 25 , 26 ].…”
Section: Discussionmentioning
confidence: 99%
“… Elimination of complement proteins and inflammatory cytokines: Supported by the efficacy of apheresis in seronegative membranous nephropathy [ 32 ]. Yabuuchi et al [ 27 ] reported a case of a 61-year-old patient with idiopathic membranous nephropathy, primarily IgG4 on kidney biopsy, and treated unsuccessfully with corticosteroids, cyclophosphamide, and cyclosporine for 2 years. Following the initiation of DFPP at a rate of two sessions per month, partial remission was achieved, with proteinuria decreasing to less than 3 g/24 h after 4 years and less than 1 g/24 h after 9 years.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations